Acute respiratory distress syndrome due to inhalation of acryloyl chloride - Takafumi Shima; Hideki Kashiwagi; Haruka Ino; Suguru Tanaka; Makiko Fukuda; Hitoshi Kobata (Acute Medicine & Surgery, 2022)
Background Acryloyl chloride is a highly toxic volatile liquid that can cause pulmonary edema. However, no sufficient treatment reports have been published to date. Here, we report a case of acute respiratory distress syndrome (ARDS) caused by acryloyl chloride inhalation. Case presentation The patient was a 36‐year‐old man with accidental exposure to acryloyl chloride. The patient had dyspnea and wet cough, with approximately 88% percutaneous oxygen saturation at room air. He was diagnosed with ARDS and admitted to the intensive care unit. Initially, he was treated with a high‐flow nasal cannula and sivelestat sodium. However, due to the possibility of delayed exacerbation, the patient was switched to methylprednisolone. Oxygenation gradually improved, and the patient was discharged on the day 8 of hospitalization. Conclusion We report the case of a patient who developed ARDS with delayed exacerbation after the inhalation of acryloyl chloride, which was treated without endotracheal intubation.